Pengaruh Aksesibilitas Lokasi Toserba Sukodadi terhadap Frekuensi Kunjungan dan Kepuasan Pelanggan - Abdullah Zawawi; Muzlifatul Jannah; Ridha Moh Ebifikka (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Location accessibility is widely recognized as an important factor influencing consumer behavior in the retail sector, particularly in traditional retail businesses that face increasing competition from modern retail formats. In the context of Toserba Sukodadi, accessibility is assumed to shape customer perceptions and subsequently influence shopping behavior. Employing a mixed-methods approach with a sequential explanatory design, quantitative data were collected from 80 customers through structured questionnaires and complemented by qualitative data obtained from in-depth interviews with selected informants. Quantitative data were analyzed using regression and path analysis, while qualitative data were examined through thematic analysis to enrich the interpretation of statistical findings. The findings reveal that location accessibility contributes positively to customer satisfaction, with road conditions and travel distance perceived as the strongest supporting factors. Customer satisfaction was also found to positively influence visit frequency and serves as a full mediating variable in the relationship between location accessibility and visit frequency. This indicates that accessibility does not directly encourage repeat visits; rather, it strengthens customer satisfaction, which subsequently increases the likelihood of revisiting the store. Qualitative findings further highlight limited parking space and store visibility as the primary issues requiring managerial attention. These results emphasize the importance of integrating physical accessibility improvements with customer-oriented service strategies to sustain customer loyalty and increase visit frequency in traditional retail businesses.